The relevance of emotional intelligence in the story «Una vida por una honra» - Aliaga Tarazona, Alexander Segundo (2020)
The purpose of this article is to emphasise the importance of emotional intelligence. In «Una vida por una honra», a story that forms part of the work Tradiciones peruanas, by Ricardo Palma, we can see the absence of good emotional management on the part of the protagonist of the story. For this reason, in this text I will address the definition of emotional intelligence and its components, as well as concepts related to it, because today more than ever the need to talk about this psychological issue arises, due to the high rate of violence that is registered in our society.